High-toughness polyacrylate binder, preparation method and application of high-toughness polyacrylate binder to silicon-based negative electrode of lithium ion battery
By using modified nanosilica and polyurethane in polyacrylate binders, stable chemical bonds are formed, the problem of insufficient toughness of existing binders is solved, and its toughness and antibacterial properties are significantly improved, and lithium ions are extended The cycle life of the battery.
Patent Information
- Application Number
- CN202411609916.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
AI Technical Summary
When used on the silicon-based negative electrode of lithium-ion batteries, the existing polyacrylate binder is insufficient in toughness and cannot effectively cope with the stress caused by volume expansion/contraction of silicon particles during charging and discharging, affecting the cycle life of the battery.
Polyurethane and nanosilica are used as toughening materials, and the reaction between modified nanosilica and polyurethane prepolymers is formed to form stable chemical bonds, and the nanosilica is connected to the polyurethane molecular chain to improve the toughness of the binder. and compatibility.
It significantly improves the toughness and tensile properties of polyacrylate binders, can absorb impact energy more effectively, extend the cycle life of lithium-ion batteries, and impart good antibacterial properties to the binder.
Smart Images

Figure CN119490807A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, and in particular to a high-toughness polyacrylate adhesive, a preparation method and application thereof to a silicon-based negative electrode of a lithium-ion battery. Background Art
[0002] The preparation process of lithium-ion batteries requires the use of binders, which are used to achieve bonding between active materials, bonding between active material layers and electrode substrates, etc. In the prior art, polyacrylate binders are mostly used as binders, but traditional polyacrylate binders have the problems of high rigidity and poor toughness. For silicon-based negative electrodes, the active material silicon particles are prone to volume expansion / contraction during the charging and discharging process. For binders with poor toughness, they cannot cope with the stress generated by the volume expansion of silicon particles, which in turn affects the cycle life of the battery. Therefore, it is necessary to improve the toughness of polyacrylate binders.
[0003] Chinese patent CN112521869B discloses a high-toughness and high-strength acrylic adhesive, which solves the rigidity problem of the acrylic adhesive by adding long-chain aliphatic methacrylic acid monomers, rubber elastomers and reinforcing resin adhesives. However, the toughening material is only an organic toughening material, and the toughening effect needs to be improved. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a high-toughness polyacrylate adhesive to solve the problem of poor toughness of the acrylic adhesive in the prior art.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a high-toughness polyacrylate adhesive comprises the following steps:
[0007] Step 1: adding nano-silica and diethylenetriaminepropyltrimethoxysilane to toluene for reaction, and after the reaction is completed, separating, purifying and drying to obtain modified nano-silica;
[0008] Step 2: Add polypropylene glycol (PPG) to acetone, stir and mix, then drop hexamethylene diisocyanate to react, cool after the reaction, add modified nano-silica, continue to react, and after the reaction is completed, rotary evaporate to obtain a composite toughening modifier;
[0009] Step 3, adding isooctyl acrylate, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, mixing them evenly to obtain a mixed monomer solution, and dividing the mixed monomer solution into a first part of the mixed monomer solution and a second part of the mixed monomer solution;
[0010] Dissolving azobisisobutyronitrile in ethyl acetate to obtain an initiator solution, and dividing the initiator solution into a first part of the initiator solution, a second part of the initiator solution and a third part of the initiator solution;
[0011] The first part of the mixed monomer solution is mixed with the first part of the initiator solution to carry out a first reaction. After the reaction is completed, the second part of the mixed monomer solution and the second part of the initiator solution are added dropwise. After the addition is completed, a second reaction is carried out. After the reaction is completed, the third part of the initiator solution is added to carry out a third reaction. After the reaction is completed, the solution is cooled to obtain a polyacrylate binder.
[0012] A composite toughening modifier is added to the polyacrylate adhesive and stirred to obtain a high-toughness polyacrylate adhesive.
[0013] Preferably, in the step 1, the mass ratio of nano-silica, diethylenetriaminopropyltrimethoxysilane and toluene is 6:(26.5-29):(80-100), and the reaction conditions are stirring and reflux reaction at a temperature of 100-120° C. for 3.5-4.5 hours.
[0014] Preferably, in the step 2, the molar ratio of polypropylene glycol to hexamethylene diisocyanate is 1:(1.1-1.2), the amount of acetone is 4-6 times the mass sum of polypropylene glycol and hexamethylene diisocyanate, and the reaction conditions are reflux reaction at 65-75° C. in a nitrogen atmosphere for 2-3 hours.
[0015] Preferably, in step 2, the amount of modified nano-silica added is 20%-30% of the mass of hexamethylene diisocyanate, and the reaction is continued under stirring at room temperature for 2.5-3.5 hours.
[0016] Preferably, in the step three, when preparing the mixed monomer, the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and ethyl acetate is (60-80):(30-40):(40-50):(20-40):(250-350), and the first part of the mixed monomer solution and the second part of the mixed monomer solution, the first part of the mixed monomer solution accounts for 20%-40% of the mass of the mixed monomer solution, and the second part of the mixed monomer solution accounts for 60%-80% of the mass of the mixed monomer solution.
[0017] Preferably, in the step three, when preparing the initiator solution, the mass ratio of azobisisobutyronitrile and ethyl acetate is (3-6):(94-97), the first part of the initiator solution accounts for 10%-30% of the mass of the initiator solution; the second part of the initiator solution accounts for 40%-80% of the mass of the initiator solution; the third part of the initiator solution accounts for 10%-30% of the mass of the initiator solution.
[0018] Preferably, in step 3, the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and azobisisobutyronitrile is (60-80):(30-40):(40-50):(20-40):(3-6).
[0019] Preferably, in step three, the conditions for the first reaction are: reaction at 60-70°C for 40-60 min, the conditions for the second reaction are: reaction at 70-80°C for 3.5-4.5 h, and the conditions for the third reaction are: reaction at 70-80°C for 4.5-5.5 h.
[0020] Preferably, in step three, the mass ratio of the polyacrylate binder to the composite toughening modifier is (90-95):(5-10).
[0021] The invention also discloses a high-toughness polyacrylate adhesive prepared by adopting the preparation method of the high-toughness polyacrylate adhesive as mentioned above.
[0022] An application of the high-toughness polyacrylate binder as described above on a silicon-based negative electrode of a lithium-ion battery.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] In the present invention, polyurethane and nano-silicon dioxide are used as toughening materials for the polyacrylate binder. Polyurethane is used as an organic toughening material, and nano-silicon dioxide is used as an inorganic toughening material. Both have good absorption capacity for impact energy and can effectively improve the toughness of polyacrylate.
[0025] In the present invention, nano-silica is modified by diethylenetriaminopropyltrimethoxysilane, so that the compatibility and dispersion uniformity between nano-silica and polyacrylate binder are good, and the toughening effect is strong; hexamethylene diisocyanate and polyether polyol are reacted to prepare polyether polyurethane, and since the ether bond has low cohesive energy and is easy to rotate, the flexible molecular chain segments of the polyether polyurethane and the molecular chains of the polyacrylate are entangled with each other, which can effectively improve the toughness of the polyacrylate;
[0026] When hexamethylene diisocyanate reacts with polyether polyol, the amount of hexamethylene diisocyanate is excessive compared with the amount of polyether polyol, that is, the obtained polyurethane prepolymer is an isocyanate-terminated polyurethane prepolymer. When nano-silica reacts with diethylenetriaminopropyltrimethoxysilane, amino groups are introduced on the surface of nano-silica. Through the reaction between the amino groups and the isocyanate groups at the ends of the isocyanate-terminated polyurethane prepolymer molecules, not only the end-capping treatment of the polyurethane prepolymer is achieved to obtain a stable polyurethane, but also the nano-silica is connected to the polyurethane molecular chain through a stable chemical bond. Through the entanglement between the polyurethane molecular chain and the polyacrylate molecular chain, the compatibility and dispersion uniformity between the nano-silica and the polyacrylate binder are further improved, and the toughening effect is further enhanced.
[0027] In addition, during the reaction of modified nano-silica and polyurethane prepolymer, the amino group reacts with the isocyanate group to form a urea group. Since urea compounds have good bactericidal activity, they give the polyacrylate adhesive good antibacterial properties, avoiding potential harm to the user's health if the adhesive is contaminated by bacteria. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The figure is a process flow chart of the preparation of the high-toughness polyacrylate adhesive of the present invention;
[0029] Figure 2 It is a bar chart showing the elongation at break test results of the high-toughness polyacrylate adhesives prepared in Examples 1-5 of the present invention and Comparative Examples 1-3;
[0030] Figure 3 A bar chart showing the tensile strength test results of the high-toughness polyacrylate adhesives prepared in Examples 1-5 of the present invention and Comparative Examples 1-3;
[0031] Figure 4 This is a bar chart showing the test results of the capacity retention rate of lithium-ion batteries made of silicon-based negative electrodes using the high-toughness polyacrylate binders prepared in Examples 1-5 of the present invention and Comparative Examples 1-3 after 300 cycles of charge and discharge. DETAILED DESCRIPTION
[0032] Example 1
[0033] This embodiment discloses a method for preparing a high-toughness polyacrylate adhesive, comprising the following steps:
[0034] Step 1, adding nano-silica and diethylenetriaminepropyltrimethoxysilane to toluene, the mass ratio of nano-silica, diethylenetriaminepropyltrimethoxysilane and toluene is 6:26.5:80, stirring and reflux reaction at 100°C for 4.5 hours, the stirring speed is 100r / min, after the reaction is completed, centrifuge at a centrifugal speed of 1500r / min for 5 minutes, wash the centrifugal precipitate with toluene 5 times, then wash it with ethanol 5 times, and place it in a vacuum drying oven at 40°C for 24 hours to obtain modified nano-silica;
[0035] Step 2: Add PPG-400 to acetone, stir and mix at a stirring speed of 150r / min for 30min, then drop hexamethylene diisocyanate, the molar ratio of PPG-400 to hexamethylene diisocyanate is 1:1.1, the amount of acetone is 4 times the mass of PPG-400 and hexamethylene diisocyanate, the dropwise addition time of hexamethylene diisocyanate is 30min, after the dropwise addition is completed, reflux reaction is carried out at 65°C in a nitrogen atmosphere for 3h, after the reaction is completed, cool to room temperature, add modified nano-silica, the amount of modified nano-silica added is 20% of the mass of hexamethylene diisocyanate, stir and react at room temperature and at a stirring speed of 500r / min for 2.5h, after the reaction is completed, remove acetone by rotary evaporation at 35°C to obtain a composite toughening modifier;
[0036] Step 3, adding isooctyl acrylate, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, wherein the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 60:30:40:20:250, and mixing them evenly to obtain a mixed monomer solution, and dividing the mixed monomer solution into a first part of the mixed monomer solution and a second part of the mixed monomer solution, wherein the first part of the mixed monomer solution accounts for 20% of the mass of the mixed monomer solution, and the second part of the mixed monomer solution accounts for 80% of the mass of the mixed monomer solution;
[0037] Dissolving azobisisobutyronitrile in ethyl acetate, wherein the mass ratio of azobisisobutyronitrile to ethyl acetate is 3:97, to obtain an initiator solution, and dividing the initiator solution into a first part of the initiator solution, a second part of the initiator solution and a third part of the initiator solution, wherein the first part of the initiator solution accounts for 10% of the mass of the initiator solution; the second part of the initiator solution accounts for 80% of the mass of the initiator solution; and the third part of the initiator solution accounts for 10% of the mass of the initiator solution;
[0038] The mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and azobisisobutyronitrile is 60:30:40:20:3;
[0039] The first part of the mixed monomer solution and the first part of the initiator solution were mixed, reacted at 60°C for 60 minutes, after the reaction was completed, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise for 2 hours, after the addition was completed, reacted at 70°C for 4.5 hours, after the reaction was completed, the third part of the initiator solution was added, reacted at 70°C for 5.5 hours, after the reaction was completed, cooled to room temperature, and a polyacrylate binder was obtained;
[0040] A composite toughening modifier was added to the polyacrylate binder, with the mass ratio of the polyacrylate binder to the composite toughening modifier being 95:5, and the mixture was stirred to obtain a high-toughness polyacrylate binder.
[0041] Example 2
[0042] This embodiment discloses a method for preparing a high-toughness polyacrylate adhesive, comprising the following steps:
[0043] Step 1, adding nano-silica and diethylenetriaminepropyltrimethoxysilane to toluene, the mass ratio of nano-silica, diethylenetriaminepropyltrimethoxysilane and toluene is 6:29:100, stirring and reflux reaction at 120°C for 3.5 hours, the stirring speed is 100r / min, after the reaction is completed, centrifuge at a centrifugal speed of 1500r / min for 5 minutes, wash the centrifugal precipitate with toluene 5 times, then wash it with ethanol 5 times, and place it in a vacuum drying oven at 40°C for 24 hours to obtain modified nano-silica;
[0044] Step 2: Add PPG-400 to acetone, stir and mix at a stirring speed of 150r / min for 30min, then drop hexamethylene diisocyanate, the molar ratio of PPG-400 to hexamethylene diisocyanate is 1:1.2, the amount of acetone is 6 times the mass of PPG-400 and hexamethylene diisocyanate, the dropwise addition time of hexamethylene diisocyanate is 30min, after the dropwise addition is completed, reflux reaction is carried out at 75°C in a nitrogen atmosphere for 2h, after the reaction is completed, cool to room temperature, add modified nano-silica, the amount of modified nano-silica added is 30% of the mass of hexamethylene diisocyanate, stir and react for 3.5h at room temperature and a stirring speed of 300r / min, after the reaction is completed, remove acetone by rotary evaporation at 35°C to obtain a composite toughening modifier;
[0045] Step 3, adding isooctyl acrylate, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, wherein the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 80:40:50:40:350, and mixing them evenly to obtain a mixed monomer solution, and dividing the mixed monomer solution into a first part of the mixed monomer solution and a second part of the mixed monomer solution, wherein the first part of the mixed monomer solution accounts for 40% of the mass of the mixed monomer solution, and the second part of the mixed monomer solution accounts for 60% of the mass of the mixed monomer solution;
[0046] Dissolving azobisisobutyronitrile in ethyl acetate, wherein the mass ratio of azobisisobutyronitrile to ethyl acetate is 6:94, to obtain an initiator solution, and dividing the initiator solution into a first part of the initiator solution, a second part of the initiator solution and a third part of the initiator solution, wherein the first part of the initiator solution accounts for 30% of the mass of the initiator solution; the second part of the initiator solution accounts for 40% of the mass of the initiator solution; and the third part of the initiator solution accounts for 30% of the mass of the initiator solution;
[0047] The mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and azobisisobutyronitrile is 80:40:50:40:6;
[0048] The first part of the mixed monomer solution and the first part of the initiator solution were mixed, reacted at 70°C for 40 minutes, after the reaction was completed, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise for 1 hour, after the addition was completed, reacted at 80°C for 3.5 hours, after the reaction was completed, the third part of the initiator solution was added, reacted at 80°C for 4.5 hours, after the reaction was completed, cooled to room temperature, and a polyacrylate binder was obtained;
[0049] A composite toughening modifier is added to the polyacrylate binder, with the mass ratio of the polyacrylate binder to the composite toughening modifier being 90:10, and the mixture is stirred to obtain a high-toughness polyacrylate binder.
[0050] Example 3
[0051] This embodiment discloses a method for preparing a high-toughness polyacrylate adhesive, comprising the following steps:
[0052] Step 1, adding nano-silica and diethylenetriaminepropyltrimethoxysilane to toluene, the mass ratio of nano-silica, diethylenetriaminepropyltrimethoxysilane and toluene is 6:27:85, stirring and reflux reaction at 110°C for 4 hours, the stirring speed is 100r / min, after the reaction is completed, centrifuge at a centrifugal speed of 1500r / min for 5 minutes, wash the centrifugal precipitate with toluene 5 times, then wash it with ethanol 5 times, and place it in a vacuum drying oven at 40°C for 24 hours to obtain modified nano-silica;
[0053] Step 2: Add PPG-400 to acetone, stir and mix at a stirring speed of 150r / min for 30min, then drop hexamethylene diisocyanate, the molar ratio of PPG-400 to hexamethylene diisocyanate is 1:1.5, the amount of acetone is 5 times the mass of PPG-400 and hexamethylene diisocyanate, the dropwise addition time of hexamethylene diisocyanate is 30min, after the dropwise addition is completed, reflux reaction is carried out at 70°C in a nitrogen atmosphere for 2.5h, after the reaction is completed, cool to room temperature, add modified nano-silica, the amount of modified nano-silica added is 25% of the mass of hexamethylene diisocyanate, stir and react for 3h at room temperature and a stirring speed of 400r / min, after the reaction is completed, remove acetone by rotary evaporation at 35°C to obtain a composite toughening modifier;
[0054] Step 3, adding isooctyl acrylate, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, wherein the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 65:32:43:25:280, and mixing them evenly to obtain a mixed monomer solution, and dividing the mixed monomer solution into a first part of the mixed monomer solution and a second part of the mixed monomer solution, wherein the first part of the mixed monomer solution accounts for 25% of the mass of the mixed monomer solution, and the second part of the mixed monomer solution accounts for 75% of the mass of the mixed monomer solution;
[0055] Dissolving azobisisobutyronitrile in ethyl acetate, wherein the mass ratio of azobisisobutyronitrile to ethyl acetate is 3.5:96.5, to obtain an initiator solution, and dividing the initiator solution into a first part of the initiator solution, a second part of the initiator solution and a third part of the initiator solution, wherein the first part of the initiator solution accounts for 15% of the mass of the initiator solution; the second part of the initiator solution accounts for 70% of the mass of the initiator solution; and the third part of the initiator solution accounts for 15% of the mass of the initiator solution;
[0056] The mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and azobisisobutyronitrile is 65:32:43:25:3.5;
[0057] The first part of the mixed monomer solution and the first part of the initiator solution were mixed, reacted at 65°C for 50 minutes, after the reaction was completed, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise for 2 hours, after the addition was completed, reacted at 75°C for 4 hours, after the reaction was completed, the third part of the initiator solution was added, reacted at 75°C for 5 hours, after the reaction was completed, cooled to room temperature, and a polyacrylate binder was obtained;
[0058] A composite toughening modifier was added to the polyacrylate binder, with the mass ratio of the polyacrylate binder to the composite toughening modifier being 94:6, and the mixture was stirred to obtain a high-toughness polyacrylate binder.
[0059] Example 4
[0060] This embodiment discloses a method for preparing a high-toughness polyacrylate adhesive, comprising the following steps:
[0061] Step 1, adding nano-silica and diethylenetriaminepropyltrimethoxysilane to toluene, the mass ratio of nano-silica, diethylenetriaminepropyltrimethoxysilane and toluene is 6:27.5:90, stirring and reflux reaction at 110°C for 4 hours, the stirring speed is 100r / min, after the reaction is completed, centrifuge at a centrifugal speed of 1500r / min for 5 minutes, wash the centrifugal precipitate with toluene 5 times, then wash it with ethanol 5 times, and place it in a vacuum drying oven at 40°C for 24 hours to obtain modified nano-silica;
[0062] Step 2: Add PPG-400 to acetone, stir and mix at a stirring speed of 150r / min for 30min, then drop hexamethylene diisocyanate, the molar ratio of PPG-400 to hexamethylene diisocyanate is 1:1.5, the amount of acetone is 5 times the mass of PPG-400 and hexamethylene diisocyanate, the dropwise addition time of hexamethylene diisocyanate is 30min, after the dropwise addition is completed, reflux reaction is carried out at 70°C in a nitrogen atmosphere for 2.5h, after the reaction is completed, cool to room temperature, add modified nano-silica, the amount of modified nano-silica added is 25% of the mass of hexamethylene diisocyanate, stir and react for 3h at room temperature and a stirring speed of 400r / min, after the reaction is completed, remove acetone by rotary evaporation at 35°C to obtain a composite toughening modifier;
[0063] Step 3, adding isooctyl acrylate, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, wherein the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 70:35:45:30:300, and mixing them evenly to obtain a mixed monomer solution, and dividing the mixed monomer solution into a first part of the mixed monomer solution and a second part of the mixed monomer solution, wherein the first part of the mixed monomer solution accounts for 30% of the mass of the mixed monomer solution, and the second part of the mixed monomer solution accounts for 70% of the mass of the mixed monomer solution;
[0064] Dissolving azobisisobutyronitrile in ethyl acetate, wherein the mass ratio of azobisisobutyronitrile to ethyl acetate is 4.5:95.5, to obtain an initiator solution, and dividing the initiator solution into a first part of the initiator solution, a second part of the initiator solution and a third part of the initiator solution, wherein the first part of the initiator solution accounts for 20% of the mass of the initiator solution; the second part of the initiator solution accounts for 60% of the mass of the initiator solution; and the third part of the initiator solution accounts for 20% of the mass of the initiator solution;
[0065] The mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and azobisisobutyronitrile is 70:35:45:30:4.5;
[0066] The first part of the mixed monomer solution and the first part of the initiator solution were mixed, reacted at 65°C for 50 minutes, after the reaction was completed, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise, the second part of the mixed monomer solution and the second part of the initiator solution were both added dropwise for 1.5 hours, after the addition was completed, reacted at 75°C for 4 hours, after the reaction was completed, the third part of the initiator solution was added, reacted at 75°C for 5 hours, after the reaction was completed, cooled to room temperature, and a polyacrylate binder was obtained;
[0067] A composite toughening modifier was added to the polyacrylate binder, with the mass ratio of the polyacrylate binder to the composite toughening modifier being 93:7, and the mixture was stirred to obtain a high-toughness polyacrylate binder.
[0068] Example 5
[0069] This embodiment discloses a method for preparing a high-toughness polyacrylate adhesive, comprising the following steps:
[0070] Step 1, adding nano-silica and diethylenetriaminepropyltrimethoxysilane to toluene, the mass ratio of nano-silica, diethylenetriaminepropyltrimethoxysilane and toluene is 6:28:95, stirring and reflux reaction at 110°C for 4 hours, the stirring speed is 100r / min, after the reaction is completed, centrifuge at a centrifugal speed of 1500r / min for 5 minutes, wash the centrifugal precipitate with toluene 5 times, then wash it with ethanol 5 times, and place it in a vacuum drying oven at 40°C for 24 hours to obtain modified nano-silica;
[0071] Step 2: Add PPG-400 to acetone, stir and mix at a stirring speed of 150r / min for 30min, then drop hexamethylene diisocyanate, the molar ratio of PPG-400 to hexamethylene diisocyanate is 1:1.5, the amount of acetone is 5 times the mass of PPG-400 and hexamethylene diisocyanate, the dropwise addition time of hexamethylene diisocyanate is 30min, after the dropwise addition is completed, reflux reaction is carried out at 70°C in a nitrogen atmosphere for 2.5h, after the reaction is completed, cool to room temperature, add modified nano-silica, the amount of modified nano-silica added is 25% of the mass of hexamethylene diisocyanate, stir and react for 3h at room temperature and a stirring speed of 400r / min, after the reaction is completed, remove acetone by rotary evaporation at 35°C to obtain a composite toughening modifier;
[0072] Step 3, adding isooctyl acrylate, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, wherein the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 75:38:48:35:330, and mixing them evenly to obtain a mixed monomer solution, and dividing the mixed monomer solution into a first part of the mixed monomer solution and a second part of the mixed monomer solution, wherein the first part of the mixed monomer solution accounts for 35% of the mass of the mixed monomer solution, and the second part of the mixed monomer solution accounts for 65% of the mass of the mixed monomer solution;
[0073] Dissolving azobisisobutyronitrile in ethyl acetate, wherein the mass ratio of azobisisobutyronitrile to ethyl acetate is 5:95, to obtain an initiator solution, and dividing the initiator solution into a first part of the initiator solution, a second part of the initiator solution and a third part of the initiator solution, wherein the first part of the initiator solution accounts for 25% of the mass of the initiator solution; the second part of the initiator solution accounts for 50% of the mass of the initiator solution; and the third part of the initiator solution accounts for 25% of the mass of the initiator solution;
[0074] The mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and azobisisobutyronitrile is 75:38:48:35:5;
[0075] The first part of the mixed monomer solution and the first part of the initiator solution were mixed, reacted at 65°C for 50 minutes, after the reaction was completed, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise for 1 hour, after the addition was completed, reacted at 75°C for 4 hours, after the reaction was completed, the third part of the initiator solution was added, reacted at 75°C for 5 hours, after the reaction was completed, cooled to room temperature, and a polyacrylate binder was obtained;
[0076] A composite toughening modifier was added to the polyacrylate binder, with the mass ratio of the polyacrylate binder to the composite toughening modifier being 91.5:8.5, and the mixture was stirred to obtain a high-toughness polyacrylate binder.
[0077] Comparative Example 1
[0078] This comparative example discloses a method for preparing a high-toughness polyacrylate adhesive, comprising the following steps:
[0079] Step 1, PPG-400 is added to acetone, and after stirring and mixing for 30 minutes at a stirring speed of 150r / min, hexamethylene diisocyanate is added dropwise, the molar ratio of PPG-400 to hexamethylene diisocyanate is 1:1.1, the amount of acetone is 4 times the mass of PPG-400 and hexamethylene diisocyanate, and the dropping time of hexamethylene diisocyanate is 30min. After the dropwise addition is completed, reflux reaction is carried out at 65°C in a nitrogen atmosphere for 3h. After the reaction is completed, the temperature is lowered to room temperature, and diethylenetriaminopropyltrimethoxysilane is added. The amount of diethylenetriaminopropyltrimethoxysilane added is 2% of the mass of hexamethylene diisocyanate. The reaction is stirred at room temperature and at a stirring speed of 500r / min for 2.5h. After the reaction is completed, acetone is removed by rotary evaporation at 35°C to obtain a toughening agent;
[0080] Step 2: adding isooctyl acrylate, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, wherein the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 60:30:40:20:250, and mixing them evenly to obtain a mixed monomer solution, and dividing the mixed monomer solution into a first part of the mixed monomer solution and a second part of the mixed monomer solution, wherein the first part of the mixed monomer solution accounts for 20% of the mass of the mixed monomer solution, and the second part of the mixed monomer solution accounts for 80% of the mass of the mixed monomer solution;
[0081] Dissolving azobisisobutyronitrile in ethyl acetate, wherein the mass ratio of azobisisobutyronitrile to ethyl acetate is 3:97, to obtain an initiator solution, and dividing the initiator solution into a first part of the initiator solution, a second part of the initiator solution and a third part of the initiator solution, wherein the first part of the initiator solution accounts for 10% of the mass of the initiator solution; the second part of the initiator solution accounts for 80% of the mass of the initiator solution; and the third part of the initiator solution accounts for 10% of the mass of the initiator solution;
[0082] The mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and azobisisobutyronitrile is 60:30:40:20:3;
[0083] The first part of the mixed monomer solution and the first part of the initiator solution were mixed, reacted at 60°C for 60 minutes, after the reaction was completed, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise for 2 hours, after the addition was completed, reacted at 70°C for 4.5 hours, after the reaction was completed, the third part of the initiator solution was added, reacted at 70°C for 5.5 hours, after the reaction was completed, cooled to room temperature, and a polyacrylate binder was obtained;
[0084] A toughening agent and nano-silicon dioxide were added to the polyacrylate binder, with the mass ratio of the polyacrylate binder, the toughening agent and the nano-silicon dioxide being 95:4.5:0.5, and the mixture was stirred to obtain a high-toughness polyacrylate binder.
[0085] Comparative Example 2
[0086] This comparative example discloses a method for preparing a high-toughness polyacrylate adhesive, comprising the following steps:
[0087] Step 1, adding nano-silica and diethylenetriaminepropyltrimethoxysilane to toluene, the mass ratio of nano-silica, diethylenetriaminepropyltrimethoxysilane and toluene is 6:26.5:80, stirring and reflux reaction at 100°C for 4.5 hours, the stirring speed is 100r / min, after the reaction is completed, centrifuge at a centrifugal speed of 1500r / min for 5 minutes, wash the centrifugal precipitate with toluene 5 times, then wash it with ethanol 5 times, and place it in a vacuum drying oven at 40°C for 24 hours to obtain modified nano-silica;
[0088] Step 2: adding isooctyl acrylate, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, wherein the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 60:30:40:20:250, and mixing them evenly to obtain a mixed monomer solution, and dividing the mixed monomer solution into a first part of the mixed monomer solution and a second part of the mixed monomer solution, wherein the first part of the mixed monomer solution accounts for 20% of the mass of the mixed monomer solution, and the second part of the mixed monomer solution accounts for 80% of the mass of the mixed monomer solution;
[0089] Dissolving azobisisobutyronitrile in ethyl acetate, wherein the mass ratio of azobisisobutyronitrile to ethyl acetate is 3:97, to obtain an initiator solution, and dividing the initiator solution into a first part of the initiator solution, a second part of the initiator solution and a third part of the initiator solution, wherein the first part of the initiator solution accounts for 10% of the mass of the initiator solution; the second part of the initiator solution accounts for 80% of the mass of the initiator solution; and the third part of the initiator solution accounts for 10% of the mass of the initiator solution;
[0090] The mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and azobisisobutyronitrile is 60:30:40:20:3;
[0091] The first part of the mixed monomer solution and the first part of the initiator solution were mixed, reacted at 60°C for 60 minutes, after the reaction was completed, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise for 2 hours, after the addition was completed, reacted at 70°C for 4.5 hours, after the reaction was completed, the third part of the initiator solution was added, reacted at 70°C for 5.5 hours, after the reaction was completed, cooled to room temperature, and a polyacrylate binder was obtained;
[0092] Add modified nano-silica to the polyacrylate binder, with the mass ratio of the polyacrylate binder to the modified nano-silica being 99.4:0.6, and stir to obtain a high-toughness polyacrylate binder.
[0093] Comparative Example 3
[0094] This comparative example discloses a method for preparing a high-toughness polyacrylate adhesive, comprising the following steps:
[0095] Step 1, PPG-400 is added to acetone, and after stirring and mixing for 30 minutes at a stirring speed of 150r / min, hexamethylene diisocyanate is added dropwise, the molar ratio of PPG-400 to hexamethylene diisocyanate is 1:1.1, the amount of acetone is 4 times the mass of PPG-400 and hexamethylene diisocyanate, and the dropping time of hexamethylene diisocyanate is 30min. After the dropwise addition is completed, reflux reaction is carried out at 65°C in a nitrogen atmosphere for 3h. After the reaction is completed, the temperature is lowered to room temperature, and diethylenetriaminopropyltrimethoxysilane is added. The amount of diethylenetriaminopropyltrimethoxysilane added is 2% of the mass of hexamethylene diisocyanate. The reaction is stirred at room temperature and at a stirring speed of 500r / min for 2.5h. After the reaction is completed, acetone is removed by rotary evaporation at 35°C to obtain a toughening agent;
[0096] Step 2: adding isooctyl acrylate, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, wherein the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, and ethyl acetate is 60:30:40:20:250, and mixing them evenly to obtain a mixed monomer solution, and dividing the mixed monomer solution into a first part of the mixed monomer solution and a second part of the mixed monomer solution, wherein the first part of the mixed monomer solution accounts for 20% of the mass of the mixed monomer solution, and the second part of the mixed monomer solution accounts for 80% of the mass of the mixed monomer solution;
[0097] Dissolving azobisisobutyronitrile in ethyl acetate, wherein the mass ratio of azobisisobutyronitrile to ethyl acetate is 3:97, to obtain an initiator solution, and dividing the initiator solution into a first part of the initiator solution, a second part of the initiator solution and a third part of the initiator solution, wherein the first part of the initiator solution accounts for 10% of the mass of the initiator solution; the second part of the initiator solution accounts for 80% of the mass of the initiator solution; and the third part of the initiator solution accounts for 10% of the mass of the initiator solution;
[0098] The mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and azobisisobutyronitrile is 60:30:40:20:3;
[0099] The first part of the mixed monomer solution and the first part of the initiator solution were mixed, reacted at 60°C for 60 minutes, after the reaction was completed, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise, the second part of the mixed monomer solution and the second part of the initiator solution were added dropwise for 2 hours, after the addition was completed, reacted at 70°C for 4.5 hours, after the reaction was completed, the third part of the initiator solution was added, reacted at 70°C for 5.5 hours, after the reaction was completed, cooled to room temperature, and a polyacrylate binder was obtained;
[0100] A toughening agent was added to the polyacrylate binder, with the mass ratio of the polyacrylate binder to the toughening agent being 95.5:4.5, and the mixture was stirred to obtain a high-toughness polyacrylate binder.
[0101] In the above embodiments and comparative examples, nano-silicon dioxide was purchased from Shanghai Naio Nano Technology Co., Ltd., with the item number NO-O-001-2 and a particle size of 500 nm; PPG-400 was purchased from Jiangsu Haian Petrochemical Plant, with the item number 00-2 and an average molecular weight of 400.
[0102] Test Case
[0103] (1) The high-toughness polyacrylate adhesives prepared in Examples 1-5 and Comparative Examples 1-3 were cast and cured at 100° C. for 10 min. The thickness of the cured sample was 100 μm. The sample was cut into 2.5×5 cm pieces for tensile testing. The test method was based on the standard GB / T1040.1-2006 “Determination of tensile properties of plastics Part 1: General Principles”. The test results are shown in Table 1:
[0104] Table 1
[0105]
[0106] As shown in Table 1, the high-toughness polyacrylate adhesive prepared by the present invention has good toughness and good tensile properties. Polyurethane and nano-silicon dioxide are used as toughening materials for polyacrylate adhesives, and nano-silicon dioxide is connected to the polyurethane molecular chain through a stable chemical bond, and has good compatibility and dispersion uniformity with the polyacrylate adhesive, good toughening effect, and large elongation at break. Nano-silicon dioxide can also have a reinforcing effect on the polyacrylate adhesive, and has high tensile strength. Compared with Example 1, in Comparative Example 1, nano-silicon dioxide is not connected by chemical bonding, and the compatibility and dispersion uniformity between nano-silicon dioxide and the polyacrylate adhesive decrease, the toughening effect decreases, and the tensile properties decrease; in Comparative Example 2, no polyurethane flexible chain is introduced, and the compatibility and dispersion uniformity between nano-silicon dioxide and the polyacrylate adhesive decrease, the toughening effect decreases, the elongation at break decreases significantly, and the tensile strength also decreases; compared with Comparative Example 1, in Comparative Example 3, nano-silicon dioxide is not added, and the elongation at break and the tensile strength are further reduced.
[0107] (2) The high-toughness polyacrylate binder prepared in Examples 1-5 and Comparative Examples 1-3 was respectively mixed with negative electrode active materials silicon dioxide (Qinghe County Chaotai Metal Materials Co., Ltd., particle size: 5000 mesh) and graphite (Lingshou County Jiushun Mineral Products Co., Ltd., particle size: 2000 mesh) in a mass ratio of 15:10:80, and deionized water was added to make the solid content of the slurry system reach 45%. The slurry was coated on a carbon-coated copper foil and dried at 80°C for 12 hours to obtain a negative electrode sheet. The obtained negative electrode sheet was assembled with a polyethylene separator, a lithium sheet, and an electrolyte into a CR2016 button battery. The battery was tested for capacity retention after 300 charge and discharge cycles at 0.5C at 25°C, and the charge and discharge voltage range was 0.01-1.5V. The test results are shown in Table 2:
[0108] Table 2
[0109]
[0110] As can be seen from Table 2, the lithium ion battery prepared by using the high-toughness polyacrylate binder prepared by the present invention as a silicon-based negative electrode binder has good cycle stability. Compared with Example 1, in Comparative Examples 1-3, due to the decrease in toughness, the cycle stability decreases, and after multiple charge and discharge cycles, the capacity retention rate decreases.
[0111] (3) The antibacterial properties of the high-toughness polyacrylate adhesives prepared in Examples 1-5 and Comparative Examples 1-3 were measured. Escherichia coli was cultured in LB broth at 37°C overnight, and then the bacteria were diluted with physiological saline to form a concentration of 1.5×10 7 CFU / mL of bacterial suspension, 100 μL of bacterial suspension was evenly coated on the LB agar plate, and the same amount of adhesive was coated on the LB agar plate containing bacteria with the same thickness, the coating diameter was 8 mm, and the LB agar plate was incubated at 37°C for 24 h to determine the antibacterial activity. The evaluation criteria were: antibacterial zone diameter: <10 mm (-), 10-12 mm (+), 13-15 mm (++), 16-21 mm (+++), and the determination results are shown in Table 3:
[0112] Table 3
[0113]
[0114] As can be seen from Table 2, the high-toughness polyacrylate adhesive prepared by the present invention has good inhibitory performance against Escherichia coli. In the reaction process of modified nano-silica and polyurethane prepolymer, the urea group generated by the reaction of amino group and isocyanate group has good antibacterial activity, and the prepared polyacrylate adhesive has antibacterial performance. Compared with Example 1, in Comparative Examples 1 and 3, when preparing the toughening agent, diethylenetriaminopropyltrimethoxysilane and terminal isocyanate polyurethane prepolymer can also generate urea groups, and the antibacterial performance is equivalent; in Comparative Example 2, no urea group is generated, and the antibacterial performance is significantly reduced.
[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-toughness polyacrylate adhesive, characterized in that: The steps include: Step 1: adding nano-silica and diethylenetriaminepropyltrimethoxysilane to toluene for reaction, and after the reaction is completed, separating, purifying and drying to obtain modified nano-silica; Step 2: adding polypropylene glycol to acetone, stirring and mixing, then dropping hexamethylene diisocyanate to react, cooling after the reaction, adding modified nano-silicon dioxide, and continuing the reaction, and rotary evaporating after the reaction to obtain a composite toughening modifier; Step 3, adding isooctyl acrylate, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate to ethyl acetate, mixing them evenly to obtain a mixed monomer solution, and dividing the mixed monomer solution into a first part of the mixed monomer solution and a second part of the mixed monomer solution; Dissolving azobisisobutyronitrile in ethyl acetate to obtain an initiator solution, and dividing the initiator solution into a first part of the initiator solution, a second part of the initiator solution and a third part of the initiator solution; The first part of the mixed monomer solution is mixed with the first part of the initiator solution to carry out a first reaction. After the reaction is completed, the second part of the mixed monomer solution and the second part of the initiator solution are added dropwise. After the addition is completed, a second reaction is carried out. After the reaction is completed, the third part of the initiator solution is added to carry out a third reaction. After the reaction is completed, the solution is cooled to obtain a polyacrylate binder. A composite toughening modifier is added to the polyacrylate adhesive and stirred to obtain a high-toughness polyacrylate adhesive.
2. The method for preparing a high-toughness polyacrylate adhesive according to claim 1, characterized in that: In the step 1, the mass ratio of nano-silica, diethylenetriaminopropyltrimethoxysilane and toluene is 6:(26.5-29):(80-100), and the reaction conditions are stirring and reflux reaction at a temperature of 100-120° C. for 3.5-4.5 hours.
3. The method for preparing a high-toughness polyacrylate adhesive according to claim 1, characterized in that: In the step 2, the molar ratio of polypropylene glycol to hexamethylene diisocyanate is 1:(1.1-1.2), the amount of acetone is 4-6 times the mass sum of polypropylene glycol and hexamethylene diisocyanate, and the reaction conditions are reflux reaction at 65-75° C. in a nitrogen atmosphere for 2-3 hours; The amount of modified nano-silica added is 20%-30% of the mass of hexamethylene diisocyanate, and the reaction is continued under stirring at room temperature for 2.5-3.5 hours.
4. The method for preparing a high-toughness polyacrylate adhesive according to claim 1, characterized in that: In the step 3, when preparing the mixed monomer, the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and ethyl acetate is (60-80):(30-40):(40-50):(20-40):(250-350); When preparing the initiator solution, the mass ratio of azobisisobutyronitrile and ethyl acetate is (3-6):(94-97).
5. The method for preparing a high-toughness polyacrylate adhesive according to claim 1, characterized in that: In the step 3, the mass ratio of isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl methacrylate and azobisisobutyronitrile is (60-80):(30-40):(40-50):(20-40):(3-6).
6. The method for preparing a high-toughness polyacrylate adhesive according to claim 1, characterized in that: In the step 3, the first part of the mixed monomer solution accounts for 20%-40% of the mass of the mixed monomer solution, and the second part of the mixed monomer solution accounts for 60%-80% of the mass of the mixed monomer solution; The first part of the initiator solution accounts for 10%-30% of the mass of the initiator solution; The second part of the initiator solution accounts for 40%-80% of the mass of the initiator solution; The third part of the initiator solution accounts for 10%-30% of the mass of the initiator solution.
7. The method for preparing a high-toughness polyacrylate adhesive according to claim 1, characterized in that: In the step 3, the conditions for the first reaction are: reacting at a temperature of 60-70°C for 40-60 minutes, the conditions for the second reaction are: reacting at a temperature of 70-80°C for 3.5-4.5 hours, and the conditions for the third reaction are: reacting at a temperature of 70-80°C for 4.5-5.5 hours.
8. The method for preparing a high-toughness polyacrylate adhesive according to claim 1, characterized in that: In the step three, the mass ratio of the polyacrylate binder to the composite toughening modifier is (90-95):(5-10).
9. A high-toughness polyacrylate adhesive prepared by the method for preparing a high-toughness polyacrylate adhesive according to any one of claims 1 to 8.
10. Use of the high-toughness polyacrylate binder as claimed in claim 9 on a silicon-based negative electrode of a lithium-ion battery.
Citation Information
Patent Citations
A high-toughness transparent two-component acrylic adhesive and its preparation method
CN112521869B